Potensi dan Peluang UMKM Terhadap Upaya Pemulihan Ekonomi di Kota Bogor Pada Era Pandemi Covid-19 - Indupurnahayu Indupurnahayu; Muhamad Fahrudin Safalah; Miranti Ayu Utami (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
In the current state of the COVID-19 pandemic, many sectors of life have stopped, including the MSME sector. This study aims to determine the potential and opportunities for Micro, Small and Medium Enterprises (MSMEs) in Bogor City in an effort to increase economic growth during the COVID-19 pandemic. The research method used is by collecting data primarily with qualitative methods whose research data is collected by distributing questionnaires to MSME actors scattered in the city of Bogor. From the research that has been done, it is found that the potential and opportunities for SMEs are very significant in an effort to increase employment, increase the value of gross domestic product, and advance the economy. Keywords: Covid-19; MSME Potential and Opportunities; and Economic Growth.